Karakteristik Mahasiswa Terhadap Pengembangan Modul Pembelajaran Kimia Berbasis STEM pada Topik Pakan Ayam Buras di Abad 21 - Made Sukaryawan; K Anom W; Jejem Mujamil (Universitas Negeri Padang, 2021)
Students need modules in 21st century learning, especially in entrepreneurship courses. The study aims to describe the characteristics of students towards the Integrated Chemistry Learning Module STEM Entrepreneurship Course in Chemistry Education Sriwijaya University, the topic of Feed for Increasing Non-Racial Chicken Eggs. This research was conducted on the third semester student in Chemistry Education Sriwijaya University with a descriptive method. The research data were collected using a valid questionnaire with a reliability coefficient of 0.925, interviews and documentation. The results of the study show that the characteristics of student are very suitable or enable or feasible to compose a learning module on the topic of Increasing Non-Racial Chicken Eggs, in the 21st century. Student responded agree and strongly agree to use this module respectively by 57.8 percent and 42.2 percent. Respondents agree and strongly agree that they are accustomed to using Android or Internet or Laptop, respectively, by 62,2 percent and 34,4 percent.